Autonomie und Verantwortung: zum moralischen Status der Arzt-Patienten-Beziehung aus philosophischer Sicht - Flickinger, Brigitte (St. Petersburg State University, Institute of Philosophy, 2018)
For almost two millennia the relationship between a physician and a patient, with regard to medical treatment, was settled according to the paternalistic moral principles laid down in the Hippocratic oath and later, in a modernized diction, in the Declaration of Geneva. With social und scientific changes occurring over the recent decades this structure lost its ethical balance and, thus, requires an amendment. Medicine is split into a curative part and a new field of scientific biomedicine, researched in laboratories independently from the relationship between a physician and a patient. While doctors have been experiencing increasing economic and legal restrictions, actual and potential patients have been tending to make use of the new medical opportunities, claiming their right to autonomous decisions. With advances made in biomedicine, the concept of health became broader and now it includes all sorts of the desired treatment (Wunschmedizin) and projective diagnosis. Today not only patients seek medical assistance, but also clients who, on the basis of their own right for autonomy, claim to have their bodily wishes fulfilled by medical practitioners. The article examines the ethical implications of these changes, with special attention paid to the concept of autonomy. Autonomy, in Kant’s enlightened deontological ethics, is the basis of such universal moral principles as the human dignity and the social responsibility. However, as can be shown, for contemporary biomedical ethics the concept of autonomy is based on libertarianism and utilitarianism. Moreover, the newly revised Declaration of Geneva neither is able to solve the moral dilemma physicians have to face choosing between professional duty and own conscience, nor can it compensate for the lack of responsibility of both sides in the relationship between a physician and a patient. Mutual respect can help to recreate a full-fledged notion of autonomy that would regain its moral value.